Liver melanomacrophage centres as indicators of A tlantic bluefin tuna, T hunnus thynnus L. well‐being - L Passantino; N Santamaria; R Zupa; C Pousis; R Garofalo; A Cianciotta; E Jirillo; F Acone; A Corriero (Journal of Fish Diseases, 2014)
Melanomacrophage centres ( MMC s), located in different organs of non‐mammalian vertebrates, play a role in the destruction, detoxification or recycling of endogenous and exogenous materials. Cytochrome P 450 monoxygenase 1 A ( CYP 1A) is involved in xenobiotics biotransformation, and its liver expression is considered as a biomarker for detecting exposure to environmental pollutants. Atlantic bluefin tuna ( ABFT ), T hunnus thynnus L., liver samples were collected from: wild animals caught in the eastern A tlantic; juveniles reared in the central Adriatic; juveniles reared in the northern Adriatic; adults reared in the western Mediterranean. The samples were processed for basic histology, histochemistry and for CYP 1 A immunodetection. An unexpected high density of MMC s, containing ferric iron and lipofuscin–ceroids, was detected in the juveniles sampled in the northern A driatic S ea. These individuals showed also a strong anti‐ CYP 1 A immunopositivity in hepatocytes and in the epithelium of bile ducts. This study supports the utility of MMC s as biomarkers of fish ‘health status’ and gives concern for a potential contaminant accumulation in ABFT .

Double Labelling Immunohistochemistry on the Nerve Fibres of Retractor Clitoridis Muscle of the Sow - F. Gazza; M. Botti; L. Bo Minelli; L. Ragionieri; F. Acone; R. Panu; G. Palmieri (Veterinary Research Communications, 2005)

Histological investigation on the ovarian cycle of the bluefin tuna in the western and central Mediterranean - A. Corriero; S. Desantis; M. Deflorio; F. Acone; C. R. Bridges; J. M. De la Serna; P. Megalofonou; G. De Metrio (Journal of Fish Biology, 2003)
The histological analysis of eastern Atlantic bluefin tuna Thunnus thynnus ovaries caught from February to September 1999–2000, made it possible to distinguish the presence of seven oocyte developmental stages and allowed the characterization of six time‐dependent ovary maturity stages. The ovaries of mature (fork length, L F ≥ 110 cm) bluefin tuna were non‐active from August (spent period) to March (quiescent period) when they contained only perinucleolar‐stage oocytes. Ovary development started in April to early May (recrudescent period) with the appearance of oocytes at the lipid stage. Vitellogenesis appeared in mid‐May (ripening period) and post‐vitellogenesis occurred in late May to mid‐June (pre‐spawning period). In late June to early July, hydrated oocytes, a sign of imminent spawning, were found only in specimens caught in Balearic waters. Females ranging between 100 and 110 cm L F , captured during the recrudescent and ripening periods, had the largest oocytes at the lipid stage, most of which were degenerating. An extensive vitellogenic atresia was observed in the ovaries of five females caught during the spawning period in non‐spawning areas.

Double Labelling Immunohistochemistry on the Peripheral Autonomic Neurons Projecting to the Bulbospongiosus Muscle in Male Impuberal Pigs - F. Gazza; F. Acone; M. Botti; L. Ragionieri; R. Panu; L. Bo Minelli; G. Palmieri (Veterinary Research Communications, 2003)